2002
DOI: 10.1016/s0160-4120(02)00015-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between speciation of Cd, Cu, Pb and Zn in sediment and their concentrations in total soft tissue of green-lipped mussel Perna viridis from the west coast of Peninsular Malaysia

Abstract: Total concentrations and speciation of cadmium (Cd), copper (Cu), lead (Pb) and zinc (Zn) in surface sediment samples were correlated with the respective metal measured in the total soft tissue of the green-lipped mussel Perna viridis, collected from water off the west coast of Peninsular Malaysia. The aim of this study is to relate the possible differences in the accumulation patterns of the heavy metals in P. viridis to those in the surface sediment. The sequential extraction technique was employed to fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(100 citation statements)
references
References 35 publications
5
88
2
4
Order By: Relevance
“…In contrast, similar results from the north reported by Amiard (2007) suggested that there is no correlation between the concentration of Zn in the labile fraction in sediment and mussels. Also Yap (2002) found the insignificant correlations between the geochemical fractions of the sediment and the soft tissue of Perna. viridis.…”
Section: Relationship Between Zn Concentration In Sediment and Soft Tmentioning
confidence: 95%
See 3 more Smart Citations
“…In contrast, similar results from the north reported by Amiard (2007) suggested that there is no correlation between the concentration of Zn in the labile fraction in sediment and mussels. Also Yap (2002) found the insignificant correlations between the geochemical fractions of the sediment and the soft tissue of Perna. viridis.…”
Section: Relationship Between Zn Concentration In Sediment and Soft Tmentioning
confidence: 95%
“…Unlike the results obtained by Apeti et al (2005) who reported that there was no significant correlation between the total Cd in the sediment and Cd in the total soft tissue of the American oyster. Although Cd coupled with the sediment in saltwater, sediment-bound Cd may be regenerated to supply the interstitial water and the overlying seawater due to changes in physico-chemical conditions (Yap et al, 2002). Among fractions, no significant correlation was found between Cd in the total soft tissue of S. cucullata and the Cd level in the acid reducible fraction of the sediment.…”
Section: Relationship Between CD Concentration In Sediment and Soft Tmentioning
confidence: 96%
See 2 more Smart Citations
“…Bu yüzden çevre kirletici maddelerin tespiti ve değerlendirilmesi için biyoindikatör kaynaklı tekniklere ilgi giderek artmaktadır. Bu yöntemle bazı kirlenme durumlarını, biyolojik sistemlerdeki değişimler ile kimyasal kalıntıları belirleyerek ortaya çıkarmak mümkün olabilmektedir [1,4,15,16]. Balarısının bitki ve çevre arasındaki bu dengeli ve hassas etkileşimini göz önünde bulundurulduklarında, ekosistemde oluşan olası değişimler bu organizmaların izlenmesi ile gözlemlenebilir [11].…”
Section: Introductionunclassified